A Study of the Revitalization of Indigenous People Annual Rituals in Taiwan - Chang, Hsiao-Ming (International Journal of Humanities and Education Development (IJHED), 2023)
Over the past 400 years, Taiwan's indigenous people annual rituals have been lost due to the assimilation of foreign regimes and the influence of modern urbanization. However, under the influence of modern social life style and political power, the annual rituals became performance and lost their original significance. But also because of its regeneration, the culture of Taiwan's indigenous people has been revitalized, and has the role of identity and continuity. However, because of the restoration of the annual rituals, the culture of the aborigines has been revitalized, and the role of recognition and continuity has been generated in Taiwan.